KEPASTIAN HADIS MUTAWATIR DAN AHAD : KAJIAN DASAR AKIDAH DAN HUKUM ISLAM - Hamzah Tacong (LPPM STAI Muhammadiyah Probolinggo, 2025)
This journal discusses the differences in the level of certainty between mutawatir and ahad hadith and their impact on establishing Islamic creed and law. The background of this study is based on the importance of ensuring the validity of Islamic sources, especially when faced with theological and legal issues that require clear evidence. This research uses a descriptive qualitative method with a literature study approach, which refers to classical and contemporary literature such as the works of al-Suyuthi, al-Baghdadi, and Ali Mustafa Ya'qub. The results of the study indicate that mutawatir hadith have a high level of certainty (qath'ī al-wurūd) and can be directly used as a basis for creed and law. In contrast, ahad hadith are strong assumptions (zhannī al-wurūd) and require further research before being used, especially in terms of belief. The discussion emphasizes that although ahad hadith are not equal to mutawatir in terms of certainty, they remain relevant in Islamic jurisprudence, especially when analyzed with the principle of maqāṣid al-syarīʿah. With the right contextual approach, ahad hadith continues to play a vital role in addressing the needs of Islamic law in the modern era.